Protein Methylation in Diabetic Kidney Disease - Cheng, Ye; Chen, Yanna; Wang, Guodong; Liu, Pei; Xie, Guiling; Jing, Huan; Chen, Hongtao; Fan, Youlin; Wang, Min; Zhou, Jun (Frontiers in Medicine, 2022)
Chronic kidney disease (CKD) is defined by persistent urine aberrations, structural abnormalities, or impaired excretory renal function. Diabetes is the leading cause of CKD. Their common pathological manifestation is renal fibrosis. Approximately half of all patients with type 2 diabetes and one-third with type 1 diabetes will develop CKD. However, renal fibrosis mechanisms are still poorly understood, especially post-transcriptional and epigenetic regulation. And an unmet need remains for innovative treatment strategies for preventing, arresting, treating, and reversing diabetic kidney disease(DKD). People believe that protein methylation, including histone and nonhistone, is an essential type of post-translational modification (PTM). However, prevalent reviews mainly focus on the causes such as DNA methylation. This review will take insights into the protein part. Furthermore, by emphasizing the close relationship between protein methylation and DKD, we will summarize the clinical research status and foresee the application prospect of protein methyltransferase (PMT) inhibitors in DKD treatment. In a nutshell, our review will contribute to a more profound understanding of DKD’s molecular mechanism and inspire people to dig into this field.